IMPLEMENTASI PERATURAN DAERAH PROVINSIRIAU NOMOR 5 TAHUN 2018 TENTANG PENYELENGGARAAN PENDIDIKAN DALAM HAL PEMENUHAN HAK ANAK AKAN PENDIDIKAN DI KOTA PEKANBARU - Irni Susanti; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Education is a conscious and planned knowledge transfer process to change humanbehavior and mature humans through the teaching process in the form of formal, non-formal, andinformal education.The main problem in this research is how is the implementation of Riau ProvinceRegional Regulation Number 5 of 2018 concerning the Implementation of Education in terms offulfilling children's rights to education in Pekanbaru City, what are the inhibiting factors for theimplementation of Riau Province Regional Regulation Number 5 of 2018 concerning EducationImplementation in terms of fulfillment children's rights to education in Pekanbaru City and whatare the government's efforts in terms of fulfilling children's rights to education based on RiauProvince Regional Regulation Number 5 of 2018 concerning the Implementation of Education inPekanbaru City.The research method used is Sociological Legal Research, namely interviews andobsevations as a data collection tool.Based on the results of the study, it is known that the implementation of the RiauProvince Regional Regulation Number 5 of 2018 concerning the implementation of education interms of fulfilling children's rights to education in Pekanbaru City has not been carried outproperly due to several things, namely improving the quality of education which is still lesseffective, education units that have not been able to Cooperating and partnering with relatedparties in accordance with the laws and regulations. Government spending on education is theamount of government spending on education (including salaries) which is allocated at least 20%of the State Budget (APBN) for the education sector. The inhibiting factors for the implementationof the Riau Province Regional Regulation Number 5 of 2018 concerning the implementation ofeducation in terms of fulfilling children's rights to education in Pekanbaru City are first, theunavailability of adequate educational facilities and infrastructure to accommodate all student.second, there are policies issued by the state, in this case the central and regional governments,which are allegedly not fully open to equal opportunities for all people to obtain education in anopen, equitable and fair manner. The government's efforts in terms of fulfilling children's rights toeducation are based on the Riau Province Regional Regulation Number 5 of 2018 concerning theimplementation of education in Pekanbaru City, namely primarily improving the quality ofeducation in terms of the Implementation of the Compulsory Education Program as referred to inparagraph (1) The Regional Government is obliged to establish a compulsory education pilot. 12(twelve) years, covering 9 (nine) years of compulsory education for basic education and 3 (three)years of compulsory education in secondary education, ensuring that every child has theopportunity to learn from basic education to secondary education as well as providing tuitionassistance costs at the secondary level. primary and secondary education in accordance with theregional financial capacity in accordance with the Riau Province Regional Regulation Number 5of the Year 2018 concerning the Implementation of Education, namely Article 42 Paragraph (2).Keywords: Implementation, Implementation of Education, Children's Right to Education